Propuesta de un sistema de gestión ambiental, basado en la norma ISO 14001:2004, para profrutas cía. Ltda., Guayaquil - Pazán Gómez, Georgina (2014)
Environmental problems caused by poor management in industries necessitate adopting solutions to limit consumption, conserve resources, reduce pollution and regulate a behavior respectful of people and the environment. Currently organizations are subject to economic, legislative, administrative or public pressures but there is great pressure from interested parties, with all this, the need to implement new ways of business management and integrate environmental variable in your decisions leading to the establishment of an environmental policy. Following this, have noticed some changes in the industry and environment related organizations integrating their environmental management systems such as ISO 14001: 2004 to identify the environmental aspects and their associated impacts and achieving continual improvement in environmental performance. Profrutas Cia. Ltda. Has adopted this management proposal for the benefits that have this tool having an Environmental Management Systems.